AGILE MARKETING: HOW TO MANAGE TEAMS AND STRATEGIES IN A FAST-CHANGING LANDSCAPE - Puji Rahayu; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
In an era defined by rapid technological change and shifting consumer behavior, traditional, rigid marketing planning cycles are increasingly inadequate. This study investigates the application of Agile methodologies, originating in software development, to marketing management to enhance team responsiveness and strategic adaptability. The objective is to identify the core principles, implementation frameworks, and organizational conditions necessary for successful Agile marketing adoption. Employing a qualitative multi-case study methodology, the research conducted semi-structured interviews with 42 marketing practitioners and leaders across eight organizations of varying sizes and industries. The results delineate a spectrum of Agile adoption, from basic tactical practices like daily stand-ups to fully embedded cultural transformations. Key findings highlight that successful implementation hinges on psychological safety, decentralized decision-making, and a shift from campaign-based to continuous value delivery. The discussion explores the tension between Agile flexibility and brand consistency, and the evolution of leadership roles from commanders to facilitators. It is concluded that Agile marketing is less a prescriptive toolkit and more a mindset essential for navigating volatility, enabling teams to learn rapidly, pivot efficiently, and sustain relevance in a dynamic marketplace. Keywords: Agile marketing, adaptive strategy, cross-functional teams, iterative planning, marketing agility.